2022
DOI: 10.1227/neu.0000000000002053
|View full text |Cite
|
Sign up to set email alerts
|

Loss to Follow-up and Unplanned Readmission After Emergent Surgery for Acute Subdural Hematoma

Abstract: BACKGROUND:Loss to follow-up (LTF) and unplanned readmission are barriers to recovery after acute subdural hematoma evacuation. The variables associated with these postdischarge events are not fully understood.OBJECTIVE:To determine factors associated with LTF and unplanned readmission, emphasizing socioeconomic status (SES).METHODS:A retrospective analysis was conducted of surgical patients with acute subdural hematoma managed operatively from 2009 to 2019 at a level 1 regional trauma center. Area Deprivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We congratulate the authors on this novel study. The use of ADI is relatively new in assessing outcomes in neurosurgery, but studies have shown that it is associated with recovery after surgery for subdural hematoma 2 and after ACDF. 3 The paper by Zhang et al 1 adds to this literature, showing, like the 2 aforementioned studies, that outcomes after lumbar spine surgery also correlate with a patient's ADI.…”
mentioning
confidence: 99%
“…We congratulate the authors on this novel study. The use of ADI is relatively new in assessing outcomes in neurosurgery, but studies have shown that it is associated with recovery after surgery for subdural hematoma 2 and after ACDF. 3 The paper by Zhang et al 1 adds to this literature, showing, like the 2 aforementioned studies, that outcomes after lumbar spine surgery also correlate with a patient's ADI.…”
mentioning
confidence: 99%
“…4 Trauma-related injuries are often associated with socioeconomically disadvantaged patients and thus therapies must recognize and address this population's needs. 5,6 As Guidry et al 1 found, insurance status is a predictor of TBI outcomes, with Medicaid patients much more likely to be lost to follow-up. This is not surprising, given the low fee-for-service Medicaid reimbursement and narrow networks within Medicaid-managed care.…”
mentioning
confidence: 99%
“…Guidry et al 1 provide an excellent study examining the factors that contribute to readmission and loss to follow-up after surgery for acute subdural hematoma. Examining these factors is important given the burden of traumatic brain injury on the United States, with over 220 000 annual hospitalizations 2 and 13.5 million individuals with TBI-related disability.…”
mentioning
confidence: 99%